Lymphocytoma cutis on the inguinal region: report of a rare case of benign lymphoproliferative disorder - Wildson Santos Craveiro Rosa; Régio José Santiago Girão; Iluska Maria Soares de Carvalho; Lana Mayara Meneses Lustosa Vargas (Sociedade Brasileira de Dermatologia, 2017)
Abstract Lymphocytoma cutis, or benign reactive lymphoid hyperplasia, is an inflammatory skin lesion that mimics clinically and histologically malignant lymphoma. Most cases are idiopathic, but they may also be triggered by multiple factors, such as insect bites, tattoos, injections and herpes zoster. Clinically, the lesions are erythematous, soft papules, plaques or nodules, usually located on the upper limbs and face. The diagnosis is mainly based on histopathology and immunohistochemistry. Corticosteroid injections, cryosurgery, PUVA therapy, radiotherapy and surgery can be therapeutic options in cases requiring immediate treatment. To demonstrate an atypical presentation of this tumor, a case lymphocytoma skin on the groin will be reported, describing its diagnosis and treatment.